Educational Achievement and Level of Aspiration among Adolescents: A Comparative Study Based on Gender, Area of Residence and Adjustment - Singh, Vijay Pratap; Sharma, Sushil Kumar (Journal of Neonatal Surgery, 2025)
The present study examined educational achievement and educational aspiration among adolescents in relation to gender, area of residence (rural and urban), and adjustment. A sample of 300 adolescents (150 boys and 150 girls) studying in Classes VIII to X was selected from government high schools in Darbhanga district, Bihar, using a purposive sampling technique. The sample included equal representation from rural and urban areas. Adjustment was assessed using the Adjustment Inventory for School Students (AISS) developed by Sinha and Singh (1984), while educational aspiration was measured using the Educational Aspiration Scale developed by Sharma and Gupta (2005). Educational achievement was assessed on the basis of marks obtained by the students in their most recent annual school examination. Independent samples t-tests were employed to analyze the data. The results revealed that girls scored significantly higher than boys on both educational achievement and educational aspiration. Urban adolescents also demonstrated significantly higher educational achievement and educational aspiration than rural adolescents. Furthermore, adjusted adolescents outperformed maladjusted adolescents in both educational achievement and educational aspiration. The findings suggest that gender, residential background and psychological adjustment are important factors associated with adolescents' academic performance and future educational goals. The study highlights the importance of providing supportive school environments, effective guidance and counselling services, and equitable educational opportunities to promote both academic success and higher educational aspirations among adolescents.....